VARIATION OF KINETIC ENERGY AND MOMENTUM CORRECTION FACTORS IN UNIFORM CIRCULAR PIPE FLOWS - Mehmet ATILGAN; Mustafa GÖLCÜ (Pamukkale University Journal of Engineering Sciences, 1996)
The effect of viscosity on the flow is generally very complex and not suitable for mathematical analysis. The shear stresses due to viscosity affect the flow velocities in pipe. On the other hand, the partial differential equations governing the flow (Navier Stokes equations) do not have general solutions. When the movement of incompressible fluids in one dimensional system is considered, the velocity of fluid at inlet and outlet sections are not one dimensional. The velocities are increasing from wall to the center and reach a maximum value at the center. So, the error in kinetic energy calculation per unit mass because of using average velocity can be corrected by a correction factor. For similar reasons, average momentum flows must also be corrected by a momentum correction factor. In this study, in uniform circular pipe flows, the kinetic energy correction factor and momentum correction factor have been investigated with respect to Reynolds number.